PROFIL GURU/DOSEN DAN TANTANGANNYA DALAM ERA PENGETAHUAN - Muhammad Khalifah Mustami (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
The knowledge era is an era of challenges and risk aversion. Therefore, in the world of education and learning should be used knowledge era as a challenge. The demands of in order to be a teacher who “SMART (Scientist, Modernist, At-tractive, Revolutionary, and Thinker)” seems to be something that must be in the knowledge era. If you don’t want to lose identity as educator and a teacher. Be-sides that, a teacher “SMART” is one form of the situation is expected to by stu-dent mall-handphone.